Analisis SWOT peningkatan daya saing pada UKM keripik nangka di Kabupaten Malang - Cahyuni Novia; Saiful Saiful; Deny Utomo (Program Studi Ilmu dan Teknologi Pangan, Universitas Yudharta, Pasuruan, 2021)
Play an important role in the growth and stabilization of the Indonesian economy (SMEs). However, SMEs are not ready, because there is still low access to markets and a lack of reliable human resources (there are still many SMEs unable to categorize their strengths, weaknesses, opportunities and threats) so that they are unable to create strategies to develop their business. The purpose of this study was to analyze the strengths, weaknesses, opportunities and threats as well as to determine the strategy to increase the power of jackfruit chips SMEs in Malang Regency. The research location is in Malang Regency. Data collection obtained from 25 respondents who are owners of the jackfruit chips SMEs in Malang Regency. The technique of data analysis using the SWOT matrix determines the priority strategies for increasing the competitiveness of jackfruit chips in Malang Regency. The results showed that efforts to improve the competitiveness of the jackfruit chips SMEs in Malang Regency could be carried out with the following strategic priorities: the best strategies to use strength to take advantage of existing opportunities are; 1) increasing the quality of jackfruit chips according to SNI, because products that have advantages do not use preservatives, 2) expanding the location of jackfruit chips marketing by utilizing technological advances for product promotion so that sales increase, 3) improving employee skills by conducting training accompanied by related institutions (government and educational institutions), 4) increase the number of jackfruit chips production by determining the selling price according to the quality produced by innovating in each production process.